Changing Pattern of Farm and Non-Farm Livelihood among the Bodos: A Study in Bodoland Territorial Areas of Assam, India - Swargiary , Prithwiraj; Mahanta, Amarjyoti (Asian Journal of Agriculture and Rural Development, 2020)
The objective of this paper is to examine the pattern and intensity of inter-generational and intra-generational changes in livelihood, taking the case of the Bodos, the largest scheduled tribe of Assam, India. The data for the study has been collected from 1161 randomly selected Bodo households in Bodoland Territorial Area Districts of Assam. The intensity of inter-generational and intra-generational livelihood changes has been measured through a rate developed for the purpose. Further, the association between the livelihood attributes has also been tested. The study finds that the intensity of intra-generational livelihood change is less than that of the inter-generational change. Livelihood change is more prominent from the farm to the non-farm sector. Though livelihood changes have taken place between the generations, the sectoral selection of livelihood by the present generation is closely associated with the livelihood of the preceding generation. Steps for infrastructure development to unfold farm and non-farm sources of income are required. Agro-based industrial units should be promoted, and required skill development initiatives should be taken so those poor households can diversify their livelihood portfolios.